MEKANISME PENGAWASAN DAN PENINDAKAN DIREKTORAT JENDERAL BEA DAN CUKAI TERHADAP PENYELUNDUPAN NARKOTIKA (Studi Kasus Penerbangan Silk Air Nomor Penerbangan Mi-152 Oleh Kantor Pengawasan Dan Pelayanan Tipe Madya Pabean B Yogyakarta) - Murti Ayu Hapsari, Triyani (GEMA, 2015)
Customs officers and airport authorities are implementing tasks as protectors of Â the people directly in the field to prevent an influx of illegal goods-psychotropic drugs that enter the customs territory through passenger and freight shipments from abroad. ability and technique Airport Customs officers in analyzing everything-psychotropic drug trafficking efforts in the process of inquiry and investigation should be owned and implemented by the Airport Customs officers.